A Dynamic Equivalent Circuit Model for Solid Magnetic Cores for High Switching Frequency Operations - Zhu,JG; Ramsden,VS (IEEE Transactions on Power Electronics, 1995)
This paper presents a dynamic equivalent circuit model of solid magnetic cores for high frequency operations in power electronic circuits. The effects of eddy current, domain wall motion, and hysteresis are taken into account by distributed equivalent resistors and distributed nonideal differential inductors, respectively. The Preisach hysteresis model is employed to simulate hysteresis effects in the inductors. A recently developed discrete transform technique based on the transmission line method is adopted to develop a discrete model for numerical dynamic analysis. The resultant model is just a simple tridiagonal system of equations. Good agreement between computer simulations and measurements has confirmed the validity of the new model. © 1995 IEEE